Evaluating the Predictive Validity of Employee Engagement: A Meta-Analytic Comparison with Job Attitudes in Forecasting Employee Performance - Awasthi, Arti; Khan, Farhina Sardar; Ali, Murad; Siddiqui, Mohd Ariz; Kumar, Anupam; Rayeen, Mohd. Shahabuddin (Journal of Management World, 2025)
The present research employs “meta-analytic estimates” to investigate if the “employee engagement (EE) construct” exhibits additional reliability in forecasting “employee performance”, which encompasses a wide range of behaviour related to performance, beyond “other job attitudes” including “job satisfaction”, “job involvement”, and “organizational commitment”. The data were obtained from 53 empirical studies conducted focusing on the correlation of the above-mentioned variables, which included a sample size of 4,421 individuals. The approximations obtained were integrated with previously published meta-analytic approximations concerning the association between “employee performance” and indicators of “job attitudes”, resulting in a meta-matrix that encompasses 1,082 distinct correlations. By utilizing the meta-matrix, it was found: (1) The additional reliability of “employee engagement” is low to moderate in comparison to “individual job attitudes”, and (2) The additional reliability of “employee engagement” is low in comparison to a “higher-order job attitude construct” that represents the amalgamation of “other job attitudes” in forecasting a “higher-order employee performance construct”. The findings indicate that due to the limited scope of prevalent “employee engagement” assessments, it may be more appropriate to view “employee engagement” as a more comprehensive “job attitude” measure that can efficiently forecast “employee performance”.